Low‐Dimensional Electrocatalysts for Acidic Oxygen Evolution: Intrinsic Activity, High Current Density Operation, and Long‐Term Stability. (29th March 2022) - Hu, Shuqi; Ge, Shiyu; Liu, Heming; Kang, Xin; Yu, Qiangmin; Liu, Bilu
Abstract: Production of green hydrogen (H2 ) by water electrolysis is important for achieving the global mission of carbon neutrality. For this, acidic water electrolysis with a higher current density operation and energy conversion efficiency compared with alkaline water electrolysis has attracted much attention. The four‐electron‐transfer oxygen evolution reaction (OER) limits the overall efficiency of water electrolysis devices. In recent years, low‐dimensional OER catalysts have been extensively explored to increase the overall efficiency of such devices, but most of them work well only at low current density and show unsatisfied long‐term stability. In this review, recent progress in acidic OER is discussed and three aspects including intrinsic activity, high current density operation, and long‐term stability are focused upon. Strategies to improve these aspects including surface chemistry engineering, constructing porous structure, and protecting the active sites' are comprehensively reviewed. Finally, prospects for developing high‐performance catalysts with high current density operation and long‐term stability for industrial applications are proposed. Abstract : Three essential features of low‐dimensional catalysts for acidic oxygen evolution reaction, including intrinsic activity, high current density operation, and long‐term stability are presented.